The relationship between primary occlusion characteristics and mouth breathing in pre-school children in Tabriz, Iran - M Kachoei; M Moghimi; A Azizi (Isfahan University of Medical Sciences, 2010)
Introduction: Malocclusion is caused by genetic, environmental, and acquired factors. Respiratory disorders and decrease of air flow in nasopharynx are known as etiologies for malocclusion. The aim of this study was to examine occlusion characteristics of preschool children in Tabriz who suffer mouth breathing.Materials and Methods: This was a cross sectional, descriptive and analytic study. Sixty four preschool children from five districts in the city of Tabriz were put into the case and the control groups. Impression from the samples were prepared and the casts were studied for arch symmetry, arch form, inter molar and inter canine width, overjet, overbite, molar relationship, posterior cross bite and crowding. Finally the data were analyzed and compared through SPSS .(α=0.05) Results: Although there were signs of malocclusion in the case group, occlusion indicators did not show any statistically significant differences between the case and the control group. Conclusion: The results of the current study show that mouth breathing does not have remarkable effects on occlusion characteristic during childhood. However, the intensity of nasal obstruction may have an influence on malocclusion.Key words: Mouth breathing, Occlusion, Malocclusion, Pre-school children.Full Text: XML PDF